The collected short stories of Louis L'Amour [large type]. Vol. 4. The adventure stories - L'Amour, Louis, 1908-1988 (Random House Large Print, 2006)
The fourth volume of Louis L'Amour's collected short stories features more than forty of the master's greatest adventure tales in a keepsake edition to cherish for generations. This unique collection gathers stories guaranteed to thrill and delight readers again and again, establishing why Louis L'Amour is truly America's favorite storyteller.